Islam and Samin: Study of the Relationship between Religion, Beliefs, and Values of the Samin Community - Mubarok, Alfi Rizkia (JUSS (Jurnal Sosial Soedirman), 2024)
This research presents a study of the relationship between religion, beliefs and values ​​of the Samin community in Bojonegoro. An ethnic community that has unique traditions and values ​​in Indonesia. This research aims to understand how Samin values ​​adapt to Islamic teachings and the interaction between the two belief systems in everyday life. This research uses social construction theory from Peter L. Berger. This theory explains a belief that also functions as a view that advertising shows ways of connecting with other humans that can be learned from studying culture and society in general. The research is based on the results of a survey conducted in Bojonegoro. The method used is sampling. Through a qualitative approach, this research identifies the challenges and synergies that arise from this relationship, as well as their impact on the identity of the Samin community.